Microencapsulation of Gulosibacter molinativorax ON4T cells by a spray-drying process using different biopolymers - Berta N. Estevinho (2017)
Molinate is a thiocarbamate herbicide used in rice crop protection.As other pesticides, molinate is a recognized environmental pollutant and bio-accumulated by some wildlife forms. Gulosibacter molinativorax ON4T is able to hydrolyse molinate into metabolites which are further degraded by other un-related bacteria. Hence, it can be used in molinate bioremediation processes. The aim of this work was to investigate the possibility of producing G. molinativorax ON4T microparticles, using different non-toxic biopolymers (arabic gum, modified chitosan, calcium alginate and sodium alginate) as encapsulating agents by a spray-drying process. Several formulations of microparticles were prepared, and their physicochemical structures were analyzed by scanning electron microscopy (SEM), laser granulometry analysis and zeta potential analysis. The obtained microparticles were evaluated considering their ability to degrade molinate, the metabolic activity (by colour development of the tetrazolium violet redox), and also the survival rate and shelf-life/storage stability of microparticles. Based on their molinate degrading activity, the biopolymers calcium alginate and modified chitosan cross-linked with tripolyphosphate appear to be the best options for the microencapsulation of the G. molinativorax ON4T. However, the microparticles produced with modified chitosan cross-linked with tripolyphosphate present the best combination of physical properties and activity degradation of molinate.